Factors Affecting The Length Of Hospital Stay For Infants With Low Birth Weight - Irene Novita Sari Tarigan; Riri Novayelinda; Ririn Muthia Zukhra (CV. AFDIFAL MAJU BERKAH, 2025)
This study investigated the factors affecting the length of hospital stay (LOS) for low birth weight (LBW) infants at Arifin Achmad Regional Hospital in 2024. Using a quantitative retrospective correlational design, the research analyzed data from the medical records of 73 LBW infants. An observation sheet served as the primary instrument, and data were analyzed using chi-square and Spearman rank correlation tests. The findings revealed a significant relationship between LOS and gestational age (p = 0.000), birth weight (p = 0.000), and the presence of complex illnesses (p = 0.000). A lower gestational age, lower birth weight, and the existence of multiple health diagnoses were all associated with a longer hospitalization period. Conversely, factors such as infant sex, feeding method, and the implementation of Kangaroo Mother Care (KMC) were not found to have a statistically significant effect on LOS. The study's primary limitation was its lack of differentiation between specific types of illnesses. Future research should consider this distinction to better inform clinical practices aimed at reducing hospitalization duration for this vulnerable population.